Enhancement of Magnetic Fluid Multimode Interference Filter-Based on No-Core Fiber in the Fourth Self-Imaging - Mahmood, Batool; Al-Dergazly, Anwaar A.; Al-Juboori, Haider (Al-Nahrain journal for engineering sciences, 2025)
Cascade single mode-No Core - single mode fiber structure (SNS) optical filters have garnered a lot of interest as dependable optical devices. These devices' simplicity, compactness, affordability, all-fiber design, low transmission loss, and ability to continuously adjust the laser wavelength at a particular spectral range contribute to their dependability. The operation's foundation is multimode interference (MMI) and self-image phenomena. SNS filter based on optimized 4th self-imaging condition for different NCF- Specifications was theoretically optimized a tunable filter based on a cascade single mode-no core-single mode (SNS) fiber structure encircled by Ferrofluid was experimentally investigated. The findings indicate that reducing the NCF diameter can enhance the filter's tunability. device has applications in fiber laser technology, spectroscopy, and optical communication.